2021
DOI: 10.1021/acsphotonics.1c01052
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Diagnostics: Past, Present, and Future

Abstract: In winter of 2020, SARS-CoV-2 emerged as a global threat, impacting not only health but also financial and political stability. To address the societal need for monitoring the spread of SARS-CoV-2, many existing diagnostic technologies were quickly adapted to detect SARS-CoV-2 RNA and antigens as well as the immune response, and new testing strategies were developed to accelerate time-to-decision. In parallel, the infusion of research support accelerated the development of new spectroscopic methods. While thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Cell-based functional microarrays are often used to gain insight into virus-host interactions by in vitro immune cell-viral interactions studies [135]. For example, the PRR of immune cells for targeted sensing of microbes is well studied using different fluorescence imaging techniques [132].…”
Section: Immune Response Toward Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-based functional microarrays are often used to gain insight into virus-host interactions by in vitro immune cell-viral interactions studies [135]. For example, the PRR of immune cells for targeted sensing of microbes is well studied using different fluorescence imaging techniques [132].…”
Section: Immune Response Toward Virusmentioning
confidence: 99%
“…However, information on the host's immune status during infection is obtained by comparing the changes in the biochemical profile of the healthy and the disease state [155,156]. An intriguing option for identifying viral infections is to apply vibrational spectroscopic techniques combined with multivariate analysis [157] because this enables the investigation of highly complex samples without the need for extensive sample preparation [135,158]. A viral infection will result in characteristic chemical changes of the affected tissue or body fluid [118].…”
Section: Study Of Host's Immune Status During Viral Infectionmentioning
confidence: 99%
“…Different viral dilutions to mimic saliva conditions were been used to detect RNA virus using Raman spectroscopy 26 . Recent studies reported the detection of SARS-CoV-2 using surface-enhanced Raman scattering (SERS) 1 , 27 32 . SERS results coupled with PCA analysis is been introduced as a powerful tool to detect the virus 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Viral infection with different incubations time has been monitored in previous studies 26,27 . Recent studies reported the detection of SARS-CoV-2 using Surface Enhanced Raman Scattering (SERS) 2,[28][29][30][31][32][33] . SERS substrate design dictates sensitivity and accuracy of the method and presents an essential key towards a successful result, but is also associated to a rather high cost of analysis [30][31][32]34 .…”
Section: Introductionmentioning
confidence: 99%